Efisiensi Boiler Berbahan Bakar Ampas Tebu PLTU PT Indolampung Perkasa Setelah Overhaul - Rosmawati Nurhasanah; Evan Satria (Sekolah Tinggi Teknik - PLN, 2015)
Boiler is the major component steam power plant in a working produce steam room with high temperature and pressure from a certain boiling water. Power plant in PT indolampung bagasse Exalted in Might be used as fuel. Even when using fuel that is different from such as in general (such as coal), component in boiler on PT indolampung like Mighty accused boiler in general. To keep performance or efficiency of boiler, need to be done Currently. Efficiency is one of the many a parameter that is used to assess whether or not good performance a boiler. Currently on PT indolampung Exalted in Might be done at any time minced ended. However, after done Currently, the recapitulation has never been done for the efficiency boiler. Therefore, the final project is to be calculated the efficiency boiler after Currently. In calculating efficiency, and used the equation boiler according to Japanese Industrial Standard (JIS) B 8222-1973, with the method heat lose. Early boiler efficiency of 75.12 percent, and the efficiency boiler this time of 74.22 percent. There was a decline boiler efficiency of 0.9 percent.